2013
DOI: 10.1002/ajh.23464
|View full text |Cite
|
Sign up to set email alerts
|

5‐Azacytidine treatment for relapsed or refractory acute myeloid leukemia after intensive chemotherapy

Abstract: Despite progress in the understanding of leukemia pathophysiology, the treatment of acute myeloid leukemia (AML) remains challenging. In patients with refractory or relapsed (R=R) AML, the prognosis is still poor and this group is targeted for new drug development. We reviewed the outcome of 47 patients, with R=R AML after at least one course of intensive chemotherapy, treated with 5-azacytidine in three different French institutions. The overall response rate was 38% including complete remission in 21%, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 23 publications
3
35
0
Order By: Relevance
“…The overall response rate was higher (38%) than in our cohort (21.7%) and the median OS (9 months) was also slightly higher than in our study (8 months). 29 However, despite the relatively inferior results compared to the French cohort using 5-azacytidine, our cohort provided a high number of patients (61 versus 47) and a similar OS to the 5-azacytidine study. Of note, randomized clinical trials are warranted in order to compare the real effectiveness of both approaches in relapsed/refractory AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…The overall response rate was higher (38%) than in our cohort (21.7%) and the median OS (9 months) was also slightly higher than in our study (8 months). 29 However, despite the relatively inferior results compared to the French cohort using 5-azacytidine, our cohort provided a high number of patients (61 versus 47) and a similar OS to the 5-azacytidine study. Of note, randomized clinical trials are warranted in order to compare the real effectiveness of both approaches in relapsed/refractory AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…122,[219][220][221][222][223][224][225][226] Enrollment in a clinical trial should therefore be the priority for such patients whenever possible. Table 8 provides recommendations for salvage regimens in patients considered fit for intensive therapy.…”
Section: Salvage Treatmentmentioning
confidence: 99%
“…235 In patients not fit for intensive salvage chemotherapy, effective treatment options are lacking. Azacitidine and decitabine induce CR rates of 16% to 21% and median survival times of 6 to 9 months in older patients with relapsed/refractory AML [223][224][225] ; median postrelapse survival after therapy with LDAC is 5 to 6 months. 226 For patients in second or third relapse, various therapeutic options are associated with CR rates of ;20% and median OS outcomes of ;3 months, 221 stressing the need for enrollment into clinical trials.…”
mentioning
confidence: 99%
“…These studies show azacitidine reduces cytopenias in select lower‐risk MDS and prolongs overall survival (OS) in higher‐risk MDS and AML,5, 6, 7, 16 may be effective maintenance therapy after induction chemotherapy (IC) or allogeneic hematopoietic stem cell transplant (alloHSCT),17, 18, 19, 20 and can induce responses in patients with relapsed/refractory disease 12, 21. Importantly, the study of azacitidine has revealed nuances of treatment with DNMTi therapy not seen with the use of traditional chemotherapy.…”
Section: Introductionmentioning
confidence: 99%